La música clásica como referente para la expresión artística con énfasis en la colorimetría, con base en la experiencia personal - Arrobo Lazo, Alex Xavier (2024)
The present research, titled CLASSICAL MUSIC AS A REFERENCE FOR ARTISTIC EXPRESSION WITH AN EMPHASIS ON COLORIMETRY, BASED ON PERSONAL EXPERIENCE, proposes the development of an abstract artistic proposal where color and form take on a symbolic role closely linked to the emotions, sensations, moods, memories, and personal experiences of the author, provoked by this musical genre. To achieve this goal, extensive qualitative research was conducted, involving the collection and analysis of bibliographic data supported by reliable sources. Applying historicist, deductive, inductive, and image analysis methods to extract information related to the theoretical, conceptual, and referential aspects of lyrical abstractionism and neoplasticism, as well as to analyze the theoretical, symbolic, and psychological aspects of color and its relationship with classical music. Finally, the experimental method was used to develop processes of artistic pre-production, production, and post-production. Upon completing the investigative process, a pictorial proposal was materialized that fuses theoretical and practical aspects, resulting from the personal reinterpretation of four classical musical tracks, incorporating characteristics similar to the work of artists Wassily Kandinsky and Piet Mondrian. Thus, it includes a wide variety of stains, colors, and forms, whose symbolic load evokes the author's individual experience during their creative processes in relation to the effects of music, without being an objective representation of reality. Keywords: Abstractionism; Lyrical Abstractionism; Neoplasticism; Classical Music; Color; Form.